Let's fill in the blanks for the given expressions.
-
For the expression \( m^{(5)} n^{(-2)} \): \[ m^{(5)} n^{(-2)} = (m^{(5)}) (n^{(-2)}) \ = (m^{(5)} \cdot \frac{1}{n^{(2)}}) \ = \frac{m^{(5)}}{n^{(2)}} \] Therefore, the blanks are: \( m^{(5)} n^{(-2)} = (m^{(5)}) (n^{(-2)}) = (m^{(5)} \cdot \frac{1}{n^{(2)}}) = \frac{m^{(5)}}{n^{(2)}} \).
-
For the expression \( j^{(-6)} p^{(-9)} \): \[ j^{(-6)} p^{(-9)} = (j^{(-6)})(p^{(-9)}) \ = \left(\frac{1}{j^{(6)}}\right) \left(\frac{1}{p^{(9)}}\right) \ = \frac{1}{j^{(6)} p^{(9)}} \] Therefore, the blanks are: \( j^{(-6)} p^{(-9)} = (j^{(-6)}(p^{(-9)}) = \left(\frac{1}{j^{(6)}}\right) \left(\frac{1}{p^{(9)}}\right) = \frac{1}{j^{(6)} p^{(9)}} \).
So the completed expressions are:
-
\( m^{(5)} n^{(-2)} = (m^{(5)}) (n^{(-2)}) = (m^{(5)} \cdot \frac{1}{n^{(2)}}) = \frac{m^{(5)}}{n^{(2)}} \)
-
\( j^{(-6)} p^{(-9)} = (j^{(-6)})(p^{(-9)}) = \left(\frac{1}{j^{(6)}}\right) \left(\frac{1}{p^{(9)}}\right) = \frac{1}{j^{(6)} p^{(9)}} \)